Building A Work Ethos To Strengthen The Independence And Resilience Of Smes During Pandemic - Sigit Tri Wahyudi; Sugeng Prayetno (Green Publisher Indonesia, 2021)
The Covid-19 pandemic is increasingly threatening the Indonesian economy (including West Java Province) and its impact can be seen clearly from the outbreak that erupted in early February 2020. Shops, retail, travel services, Micro-Small and Medium Enterprises (hereinafter referred to as SMEs) and Small and Medium Industries (Many SMEs in West Java have closed. This study aims to build a work ethic to strengthen the Independence and Resilience of MSMEs during the Pandemic in Bekasi City. This type of research is descriptive qualitative that uses the type of research in the form of Document Study. The location of this research was carried out in MSMEs in the culinary field around Bekasi City starting in May 2021. Based on the results of a simple linear regression test, the results of this study concluded that the Covid-19 variable has an effect on microenterprise variables, small and medium. It is here every increase of one unit of will hamper the economy so that the income of micro, small and medium enterprises in Bekasi City decreases. The strategy of Micro, Small and Medium Enterprises facing Covid-19 to continue their business continuity is to increase the sales volume of each SMEs by applying conventional marketing strategies to online marketing and using social media as an online channel